The effect of nurses’ occupational safety perceptions on job satisfaction: a research study conducted in Turkey - Gulfer Bektas; Kubra Say Kulalar; Vesile Unver (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the effect of nurses’ occupational safety perceptions on the level of job satisfaction. Method: The cross-sectional study was conducted at Acibadem Healthcare Group hospitals in Turkey from January 15 to February 15, 2018, and comprised of professional nurses. Data was collected using the Job Satisfaction Scale and the Occupational Health and Safety Culture Scale. Data was analysed using SPSS 21. Results: Of the 275 nurses, 210(76.4%) were females and 65(23.6%) were males. The overall mean age was 26.50±5.11 years, mean working experience was 57.08±51.56 months and the mean length of current employment was 31.13±32.86 months. There was a positive correlation between nurses’ job satisfaction and occupational safety perceptions (p<0.001); between nurses’ working conditions and extrinsic satisfaction (p=0.001); and between the working conditions and the nurses’ general satisfaction (p=0.008). Conclusion: High perceptions of occupational safety among the nurses led to greater job satisfaction within the organisation. Also, working conditions had a direct impact on both extrinsic and general job satisfaction. Key Words: Occupational safety, Job satisfaction, Nursing, Working conditions. Continuous...